Arterial access complications in patients with extracorporeal membrane oxygenation – literature review - Nóbrega, Leandro (2024)
INTRODUCTION: The use of extracorporeal membrane oxygenation (ECMO) has been increasing in recent years. Veno-Arterial ECMO (ECMO-VA) is usually deployed in refractory cardiac failure and is mostly cannulated through the common femoral artery. When present, arterial access complications may have important consequences in these patients. Therefore, this work aims to narratively review the available evidence regarding the impact of arterial access complications in patients undergoing ECMO-VA. METHODS: A Medline search was performed to identify articles focused on arterial access complications in patients undergoing ECMO-VA since 2010. The keywords were “extracorporeal membrane oxygenation,” “arterial access,” and “complications.” The primary endpoints were the description of the arterial complication with demographic characteristics and the short- and long-term prognosis. RESULTS: The incidence of vascular complications in patients undergoing ECMO-VA ranges from 9.4% to 43.9%. In the majority of retrospective studies, their presence isn’t associated with increased mortality. However, in a meta-analysis, there was an increased mortality in patients with complications (RR 1.36; CI 95% 1.15-1.60; P=0.0004). The main risk factors are peripheral artery disease and female sex, while the reduced case volume can be associated with increased complications. CONCLUSION: Most available evidence on managing arterial complications associated with ECMO derives from retrospective studies. To decrease the risk of access complications, protocols for cannulation, surveillance, and decannulation should be elaborated. Prospective studies are needed to improve the prevention and management of vascular access complications in patients under ECMO-VA.